The Legal Challenge of Marital Rape: Bridging Islamic Law and Indonesia's Anti-Violence Statute - Masduki Masduki; B. Syafuri; Ahmad Hidayat (KARSA Journal of Social and Islamic Culture, 2025)
In Islamic law, there are two views on marital rape: one rejects it because marriage is considered a lifelong consent to sexual relations. At the same time, the other recognizes the possibility of marital rape within a marriage. Unlike UU-PKDRT, marital rape receives strict penalties. This study aims to identify and analyze the legal sanctions for marital rape in UU-PKDRT and Islamic criminal law, compare the sanctions of both laws, and explain the concept of takzir for marital rape. The research method is juridical-normative, using qualitative data and three frameworks: credo theory, legal change, and takzir. The study results show that UU-PKDRT, which includes marital rape, does not contradict Islamic law and therefore should be obeyed by Ulil Amri. The legal sanctions are relevant and in accordance with takzir; sexual relations are a mutual right of husband and wife, and forced sexual relations in marriage are not considered rape but violence that can be sanctioned by takzir; marital rape is not considered rape in Islam because marriage negates fornication; Marital rape in UU-PKDRT is viewed as rape, but in Islamic law, it is only violence that can be sanctioned by takzir after reconciliation efforts. The new theory from this research states that marital rape is violence, not rape.